2023
DOI: 10.3390/vaccines11020392
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy to Receive the Second COVID-19 Vaccine Booster Dose among Older Adults in Hong Kong: A Random Telephone Survey

Abstract: A second COVID-19 vaccine booster dose is effective and safe for older adults. This study investigated hesitancy to take up a second COVID-19 vaccine booster dose and its determinants among older adults in Hong Kong. Participants were Chinese-speaking community-dwelling adults aged 65 years or above. Telephone numbers were randomly selected from up-to-date telephone directories. A total of 370 participants completed the telephone survey. Logistic regression models were fitted for data analysis. Among the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Numerous studies that focus on the elderly have identified several factors associated with hesitancy toward receiving the booster dose of the COVID-19 vaccine, such as a self-perceived low susceptibility to COVID-19 [ 12 ], perceived barriers to obtaining the booster [ 12 , 13 ], a perceived lack of benefits from receiving the booster dose [ 12 ], and having a negative attitude toward vaccines [ 14 ]. Other factors reported include the belief that the first or second dose of COVID-19 vaccine is sufficient [ 15 ], prior receipt of the Sinovac COVID-19 vaccine [ 15 ], experiencing side effects [ 15 ], the perception that the vaccine is ineffective in preventing COVID-19 [ 15 ], and facing “vaccine fatigue” due to receiving repeated COVID-19 vaccination [ 13 , 15 ]. In addition, demographic background, such as being female [ 13 ] and a younger age [ 16 , 17 ] appear to play a role in shaping attitudes towards COVID-19 booster vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies that focus on the elderly have identified several factors associated with hesitancy toward receiving the booster dose of the COVID-19 vaccine, such as a self-perceived low susceptibility to COVID-19 [ 12 ], perceived barriers to obtaining the booster [ 12 , 13 ], a perceived lack of benefits from receiving the booster dose [ 12 ], and having a negative attitude toward vaccines [ 14 ]. Other factors reported include the belief that the first or second dose of COVID-19 vaccine is sufficient [ 15 ], prior receipt of the Sinovac COVID-19 vaccine [ 15 ], experiencing side effects [ 15 ], the perception that the vaccine is ineffective in preventing COVID-19 [ 15 ], and facing “vaccine fatigue” due to receiving repeated COVID-19 vaccination [ 13 , 15 ]. In addition, demographic background, such as being female [ 13 ] and a younger age [ 16 , 17 ] appear to play a role in shaping attitudes towards COVID-19 booster vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors reported include the belief that the first or second dose of COVID-19 vaccine is sufficient [ 15 ], prior receipt of the Sinovac COVID-19 vaccine [ 15 ], experiencing side effects [ 15 ], the perception that the vaccine is ineffective in preventing COVID-19 [ 15 ], and facing “vaccine fatigue” due to receiving repeated COVID-19 vaccination [ 13 , 15 ]. In addition, demographic background, such as being female [ 13 ] and a younger age [ 16 , 17 ] appear to play a role in shaping attitudes towards COVID-19 booster vaccination. It has also been noted that personal issues such as forgetfulness and lack of time contribute to compliance failure [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The background characteristics, such as perceived benefits, cues to action, and perceived self‐efficacy of receiving the second booster dose, were associated with lower vaccine hesitancy. Perceived barriers to fatigue from receiving repeated COVID‐19 vaccinations were associated with higher vaccine hesitancy 18 . Another study in Hong Kong showed that 31.6% of older adult participants received a COVID‐19 vaccine booster dose 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Perceived barriers to fatigue from receiving repeated COVID‐19 vaccinations were associated with higher vaccine hesitancy. 18 Another study in Hong Kong showed that 31.6% of older adult participants received a COVID‐19 vaccine booster dose. 19 In a study conducted in the United States, the acceptance of the booster dose among healthcare workers was 83.6% when asked about acceptance of a hypothetical yearly booster vaccine to maintain immunity.…”
Section: Introductionmentioning
confidence: 99%